Clinical Indications Of Gandhaka Rasayana An Experiential And Scientific View - Shripathi , Acharya G; Acharya, Miss Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2021)
Herbal and Herbo mineral formulations are commonly used in the treatment of various disorders by Ayurveda physicians in India and Indian subcontinent. They are potent in action when compared to herbal formulations. Arogyavardhini vati, Mrityunjaya rasa, Pravala panchamrita rasa, Kamadugha rasa, Agnitundi rasa, and vrinapahari rasa are few Rasaushadhi (Herbo mineral) formulations which are commonly used in the management of non-communicable disorders. Gandhaka rasayana is a herbo mineral formulation which is commonly used in skin and urinary tract disorders. It is given in Mootrakricchra (Dysuria), Mootradaha (Burning micturition), UTI, and skin disorders like scabies, furunculosis, Taenia infection, Padadari, (Cracked heels) paronychia etc. It is having actions like dipana (appetizer) pachana (digestives), krimighna (anthelmintics), anti-infective, antibacterial, bactericidal, antimicrobial Rasayana (Rejuvenator) and immunomodulator actions. The present paper highlights about the clinical indications of Gandhaka rasayana in an experiential and scientific view.